Assessing the Multichannel Impact of Brand Store Entry by a Digital-Native Grocery Brand - Van Crombrugge, Michiel; Breugelmans, Els; Breiner, Florian; Scheiner, Christian W. (Journal of Marketing, 2024)
For digital-native fast-moving consumer goods (FMCG) manufacturers that sell through their own online channel and have made headway into supermarkets, brand stores can represent the next step in a multichannel distribution strategy. In this research, the authors investigate the impact of introducing a brand store on a digital-native FMCG brand's sales in its existing company-owned online channel and in independent supermarkets, as well as on the brand's supermarket distribution. By incorporating brand store sales and operational costs, this research also specifies the entry effects on the brand's top-line total brand sales and bottom-line operating profit. Based on before-and-after-with-control-group analyses of the entry of ten brand stores by a digital-native FMCG brand, the authors show that brand store entry boosts supermarket sales, partially driven by a brand store's positive effect on the number of supermarkets listing the brand. Although they cannibalize company-owned online sales, brand store entries generate an influx of own brand store sales that offset online channel losses. Still, accounting for brand stores’ operational costs reveals that top-line growth is not always enough to preserve the bottom line.